An Examination on the Concept of Adverbial Complement and Teaching It - Esra Ekinci Çelikpazu; Tuğba Karakayalı (Elementary Education Online, 2023)
It is seen that one of the most important problems students experience in the teaching process of grammar is the complexity of grammatical concepts. One of the grammatical concepts that students experience in confusion is the concept of adverbial complement. In this study, problems related to teaching the concept of adverbial complement were presented by examining what the concept covers, its scope and how it is taught at secondary school level and various solutions were proposed to these problems. The model of the study is case analysis and a semi-structured interview technique was used as a data collection method. The study group of the research was 22 Turkish language teachers working in different cities. A semi-structured interview form was applied to Turkish language teachers and teachers’ opinions about the concept of adverbial complement and problems related to teaching it were analyzed by content analysis. Descriptive analysis was conducted to reveal the scope of the concept of "adverbial complement" and its content reflected in secondary school teacher guidebooks. The results of the study showed that the instructions and activities included in teacher guidebooks overlap with the data obtained from the interviews with the teachers in terms of naming and definition of adverbial complement, what it describes and teaching problems / inconsistencies. It has been suggested that syntactic relations should be used in both denotations and sentence analyses in order to reduce the problems related to the teaching of grammatical concepts.